Antibakteri Fraksi n-Heksana Kulit Hylocereus polyrhizus Terhadap Staphylococcus epidermidis dan Propionibacterium acnes - Sri Wardaningsih; Eka Kartika Untari; Yunita Fauziah (Universitas Indonesia, 2014)
Acne can be caused by Propionibacterium acnes and Staphylococcus epidermidis. Using antibiotic for the acne theraphy in a long term period can cause resistance, organ detriment and imunohypersensitivity. Red dragon fruit's peel (Hylocereus polyrhizus) is one of natural materials which can be used for alternative antibacterial. The aim of this study was to determine the antibacterial activity of n-Hexane fraction of red dragon fruit's peel against S. epidermidis dan P. acnes with the method of disc diffusion Kirby-Bauer. Red dragon fruit's peel powder was macerated with chloroform and then fractionated with n-Hexane. The result of phytochemical screening showed that red dragon fruit's peel contained terpenoid and alkaloid. Clindamycin 4µg/disk was used for positive control while DMSO 10% was used for negative control. Data was analyzed using R-Commander program 3.0.3 version. This research showed that n-Hexane fraction of red dragon fruit's peel had antibacterial activity against P. acnes where the average zone of inhibition obtained from the concentrations of 20; 40; and 80 mg/mL were 9 mm; 10,25 mm; and 10,5 mm, respectively. However, n-Hexane fraction of red dragon fruit's peel didn't have antibacterial activity against S. epidermidis.